2006
DOI: 10.1128/aac.00313-06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofPlasmodium falciparumGrowth In Vitro and Adhesion to Chondroitin-4-Sulfate by the Heparan Sulfate Mimetic PI-88 and Other Sulfated Oligosaccharides

Abstract: A panel of sulfated oligosaccharides was tested for antimalarial activity and inhibition of adhesion to the placental malaria receptor chondroitin-4-sulfate (CSA). The heparan sulfate mimetic PI-88, currently undergoing phase II anticancer trials, displayed the greatest in vitro antimalarial activity against Plasmodium falciparum (50% inhibitory concentration of 7.4 M) and demonstrated modest adhesion inhibition to cell surface CSA.Some of the severe pathophysiological symptoms of Plasmodium falciparum infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Negatively charged polysaccharides, such as heparin, chondroitin and dextran sulfates, fucoidan, and the nonsulfated glycosaminoglycan (GAG) hyaluronan, block cytoadhesion of pRBCs to various host receptors 7 8 9 10 and disrupt P. falciparum rosettes 11 12 . Heparin and related sulfated polysaccharides possess antimalarial activity that has been described to operate through inhibition of RBC invasion by merozoites 9 13 14 15 16 .…”
mentioning
confidence: 99%
“…Negatively charged polysaccharides, such as heparin, chondroitin and dextran sulfates, fucoidan, and the nonsulfated glycosaminoglycan (GAG) hyaluronan, block cytoadhesion of pRBCs to various host receptors 7 8 9 10 and disrupt P. falciparum rosettes 11 12 . Heparin and related sulfated polysaccharides possess antimalarial activity that has been described to operate through inhibition of RBC invasion by merozoites 9 13 14 15 16 .…”
mentioning
confidence: 99%
“…Polysulphated heparin-like-molecules (HLMs) are inhibitory to invasion (Boyle et al, 2010a) and may have potential as antimalarial agents (Havlik et al,1994(Havlik et al, , 2005Clark et al, 1997;Evans et al, 1998;Adams et al, 2006;Boyle et al, 2010a). From testing a number of modified HLMs and semi-synthetic carbohydrates based on K5 polysaccharides that have different compositions, it has been previously shown that the invasion-inhibitory activity of these compounds is specific and dependent on the level and degree of sulphation, as well as backbone structure and chain length (Boyle et al, 2010a).…”
Section: Inhibitors Of Invasion As Novel Therapeutic Agentsmentioning
confidence: 97%
“…A small amount of the anticoagulent agent, heparin, was introduced into the diagnostic channel from the heparin-coated capillary tube used for collecting blood sample. This was done to suppress blood coagulation before loading the blood into the diagnostic channel (Adams et al 2006;Xiao et al 1996). Removing heparin from the sample was necessary because it could alter the surface morphology of the cell membranes (Freidlin 1985).…”
Section: Microplatform Designmentioning
confidence: 99%